The moderating effect of perceived risk on users' continuance intention for FinTech services - Kshitiz Jangir; Vikas Sharma; Sanjay Taneja; Ramona Rupeika-Apoga (Journal of Risk and Financial Management, 2023)
The study's aim is to investigate how FinTech users' perceived risk influences their continuance intention to use FinTech services. The new model, which was based on the Expectation Confirmation Model, was created to achieve the study's aim. The Partial Least Square Structural Equation Model was used to investigate the proposed model and the relationship between the adopted constructs. The sample consists of 802 individual survey responses from northern India from April to June 2022. The proposed model explains 45.4% of the variance in the continuance intention of FinTech users, which is significantly influenced by perceived usefulness and satisfaction. Furthermore, perceived risk, as a moderator, significantly moderates continuance intention through satisfaction and satisfaction through confirmation. However, perceived risk was found to have an insignificant moderating effect on the relationship between perceived usefulness and satisfaction as well as perceived usefulness and continuance intention. The findings provide insights to FinTech service providers about the factors that influence users' intent to continue using FinTech services.
Keywords: 650; FinTech; PLS-SEM; perceived risk; continuance intention; Expectation Confirmation Model; moderator